2015
DOI: 10.2217/pgs.15.34
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Rs1051730–Rs16969968 Variant and Smoking Cessation Treatment: A Meta-Analysis

Abstract: There is no robust evidence that allelic variations of rs16969968 or rs1051730 are associated with smoking cessation after NRT. Original submitted 26 November 2014; Revision submitted 9 March 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Rs1051730, a SNP in CHRNA3 , which encodes the alpha-3 nicotinic receptor (13, 27), was first identified in genomewide association studies (GWAS) as a contributor to the heaviness of smoking (28, 29). Despite subsequent studies showing that the rs1051730*T allele reduces the probability of cessation success among treatment-seeking smokers (30, 31), a recent large study (32) and a meta-analysis (33) showed no effect of the SNP on the response to nicotine replacement therapy. Another polymorphism in the chromosome 15 cluster, rs16969968, which maps to CHRNA5 , has been associated with both heaviness of smoking and nicotine dependence (30, 31).…”
Section: Precision Medicine: Advances In Oncologic Cardiovascular Amentioning
confidence: 91%
See 1 more Smart Citation
“…Rs1051730, a SNP in CHRNA3 , which encodes the alpha-3 nicotinic receptor (13, 27), was first identified in genomewide association studies (GWAS) as a contributor to the heaviness of smoking (28, 29). Despite subsequent studies showing that the rs1051730*T allele reduces the probability of cessation success among treatment-seeking smokers (30, 31), a recent large study (32) and a meta-analysis (33) showed no effect of the SNP on the response to nicotine replacement therapy. Another polymorphism in the chromosome 15 cluster, rs16969968, which maps to CHRNA5 , has been associated with both heaviness of smoking and nicotine dependence (30, 31).…”
Section: Precision Medicine: Advances In Oncologic Cardiovascular Amentioning
confidence: 91%
“…Another polymorphism in the chromosome 15 cluster, rs16969968, which maps to CHRNA5 , has been associated with both heaviness of smoking and nicotine dependence (30, 31). However, a recent meta-analysis (33) showed no association between rs16969968 and the response to smoking cessation treatment. Thus, the existing research linking nAChRs genetic variants to response to nicotine dependence treatments remains inconclusive (12).…”
Section: Precision Medicine: Advances In Oncologic Cardiovascular Amentioning
confidence: 99%
“…This is reflected in a recent meta-analysis to examine only smokers receiving nicotine replacement therapy without a control group where rs16969968 or rs1051730 showed no association with smoking abstinence [89]. In another recent trial of smokers of European ancestry, CHRNA5-A3-B4 gene variants exhibited a trending, but not significant association with smoking cessation in smokers receiving placebo; however, there was no association with another robust predictor, nicotine metabolism ratio (NMR), in this same group [68].…”
Section: Genetics Of Smoking Cessation Treatment Responsementioning
confidence: 99%
“…We believe that such variability reflects the actions of important moderators related to treatment and sample characteristics. While the Leung et al [1] study was not intended to detect such moderation, we believe that further research on such effects is needed for a methodologically principled approach to the application of Precision Medicine in order to best help out patients quit smoking. …”
mentioning
confidence: 99%
“…The article by Leung et al [1] provides a metaanalysis of CHRNA5-CHRNA3-CHRNB4 rs16969968-rs1051730 and smoking cessation in the context of six treatment trials where all participants received nicotine replacement therapy. The authors found no evidence of significant association between the variant and successful smoking cessation, and in keeping with this, the authors conclude that "the alleles of rs1051730 and rs16969968 are not associated with smoking cessation."…”
mentioning
confidence: 99%